Теоретико-методологічні аспекти оцінки результативності сільського туризму - Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна; Bakina, Tetiana; Грибова, Д. В; Захарченко, Олена Григорівна; Захарченко, Елена Григорьевна; Zakharchenko, Olena (My University, 2019)
UK: У статті проаналізовано особливості оцінки результатів туристичної діяльності у сільській місцевості. Доведено важливість розвитку туристичного бізнесу на базі сільських домогосподарств. Обґрунтовано значущість сільського туризму як форми самозайнятості населення. Сформульовано основні методологічні принципи оцінки результатів діяльності у сфері сільського туризму. Доведено необхідність урахування соціально-економічного складника функціонування сільських домогосподарств в оцінці їхньої діяльності у сфері туризму. Обґрунтовано доцільність застосування дворівневої системи оцінки результатів діяльності суб’єктів сільського туризму: на рівні господарства та в масштабі сільської громади. Запропоновано комплекс показників для аналізу характеру функціонування сфери сільського туризму в економічному та соціальному аспектах. RU: В статье проанализированы особенности оценки результатов туристической деятельности в сельской местности. Доказана важность развития туристического бизнеса на базе сельских домохозяйств. Обоснована значимость сельского туризма как формы самозанятости населения. Сформулированы основные методологические принципы оценки результатов деятельности в сфере сельского туризма. Доказана необходимость учета социально-экономической составляющей функционирования сельских домохозяйств в оценке их деятельности в сфере туризма. Обоснована целесообразность применения двухуровневой системы оценки результатов деятельности субъектов сельского туризма: на уровне хозяйства и в масштабе сельской общины. Предложен комплекс показателей для анализа характера функционирования сферы сельского туризма в экономическом и социальном аспектах. EN: The role of small business as an element of national economy is considered in the article. It is noted that small agrarian units to some extent restrains rural depopulation processes. It is proved that the current state is the result of holding agricultural lands from being included in fullfledged economic turnover. The necessity to analyze the future prospects of economic self-realization of family forms of agrarian entrepreneurship is emphasized. The relevance of the analysis of the direction of rural tourism as a form of reorientation of peasant farms is substantiated. The article analyzes the features of the evaluation of the results of tourism activities in rural areas. The importance of developing tourism businesses based on rural households has been proved. The importance of rural tourism as a form of self-employment of the population is substantiated. The basic methodological principles of evaluation of results of activity in the field of rural tourism are formulated. The necessity of taking into account the socio-economic component of the functioning of rural households in the evaluation of their activity in the field of tourism has been proved. The feasibility of applying a twotier system for evaluating the performance of rural tourism entities is substantiated: at the farm level and across the rural community. A set of indicators is proposed to analyze the nature of rural tourism in the economic and social aspects. It is noted that the assessment of the results of activity at the level of a particular household should provide for adequate compensation of the physical labor costs of the household members. The desirability of using the “desirable income” indicator as an alternative to wages is indicated. The possibility of calculating the indicators of conditional income and conditional profitability for evaluating the efficiency of family forms of rural tourism has been proved. The prospect of application of the research results in the process of developing regional programs to stimulate the effective functioning of small businesses in the countryside and rural development is substantiated.
Theoretical-methodological aspects of assessment of rural tourism results
Keywords: туристична діяльність; середній клас; методологія; сільські території; ефективність; туристическая деятельность; средний класс; методологий; сельские территории; эффективность; tourism; middle class; methodology; rural areas; efficiency